PROBLEMATIKA SANTRI DALAM MENGHAFAL AL-QURAN DI LEMBAGA TAHFIZ AL QU’RAN TUNAS HAFIZAH SIHITANG PADANGSIDIMPUAN - Eka Damayanti Nasution; Syamsuddin Muir; Satrio Abdillah; Sawaluddin Siregar (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This study aims to determine the problems students encounter when memorizing the Quran at Tahfiz Al-Quran Tunas Hafizah Sihitang Padangsidimpuan Academy. The method used in this study is qualitative description. Memorizing the Quran is a process of protecting, protecting and maintaining the sanctity of the Quran. Allah says in Surah Al-Kamar, verse 17 of the Quran, that He has indeed made learning and memorizing the Quran easier. Research results show that students who memorize the Quran face various problems while memorizing the Quran. It is possible to distinguish two types of problems, which are internal problems (inside the self) and external problems (outside the self), which are laziness, feelings of impatience and hopelessness, without ability to organize and use time wisely, inability to maintain discipline in tahfiz. activity, forgetfulness, unethical behavior, problems with the physical and social environment, etc